2011
DOI: 10.1245/s10434-011-2046-z
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Localization of Parathyroid Adenomas with Magnetic Resonance Imaging at 3.0 T: An Adjunct Method to Supplement Traditional Imaging

Abstract: MRI is an excellent adjunct for preoperative parathyroid localization. The advent of improved fat suppression techniques in the neck, including chemical shift-based water-fat separation, is critical to its utility. Although time-resolved MRI was not always helpful, it was crucial in certain cases. It may prove to be more useful with the development of faster scanning techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 37 publications
2
47
0
3
Order By: Relevance
“…The use of MRI allows the evaluation of parathyroid anatomy, detection of ectopic glands, in the absence of patient's radiation exposure; reported sensitivity is 80% with the 1.5 T magnets (14). Better visualization has recently been obtained with the use of 3.0 T MRI magnet as a valid method for parathyroid lesions identification, particularly in PHPT patients with negative first-line imaging (15,16 About 30 years ago, when we started to be interested in PHPT (17), the only clinical task was to make the diagnosis. Imaging of the parathyroid glands was an almost unexplored field and patients were immediately referred to the surgeon with expertise in neck operation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of MRI allows the evaluation of parathyroid anatomy, detection of ectopic glands, in the absence of patient's radiation exposure; reported sensitivity is 80% with the 1.5 T magnets (14). Better visualization has recently been obtained with the use of 3.0 T MRI magnet as a valid method for parathyroid lesions identification, particularly in PHPT patients with negative first-line imaging (15,16 About 30 years ago, when we started to be interested in PHPT (17), the only clinical task was to make the diagnosis. Imaging of the parathyroid glands was an almost unexplored field and patients were immediately referred to the surgeon with expertise in neck operation.…”
Section: Introductionmentioning
confidence: 99%
“…These sequences provide excellent fat suppression with signal-to-noise ratio superior to that of short-tau inversion recovery sequences (STIR). Using IDEA L sequences, Grayev et al [54] recently reported a low sensitivity (64 %), but had the ability to detect a few adenomas that were missed by sestamibi. We reported high frequency (95.7 %) of hyperintensity on T2-weighted IDEAL FSE images, suggesting that a high T2 signal is the feature to be used to localise a structure that is suspected of representing a PTA.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, an agreement about a post-contrast sequence protocol has not been reached. The previously proposed use of TRICKS led to an increased temporal resolution, but with decreased spatial resolution [51], and to just a modest improvement in PTA detection in comparison with T2-weighted IDEAL FSE sequences [54]. Our post-contrast protocol was optimised in order to perform quite rapid sequences, at the same time maintaining a high spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4D CT has shown superior accuracy compared with scintigraphy, 3 though the radiation dose remains as high as 5.56 -10.4 mSv. [4][5][6] MR imaging is an attractive alternative to both scintigraphy and 4D CT due to the lack of radiation and has been used for the evaluation of PTAs with some success, [7][8][9] though not with the same effectiveness as 4D CT. Traditional technical limitations to localizing PTAs with MR imaging have recently been addressed with modern MR imaging technology.…”
mentioning
confidence: 99%